Analysis of Professional Ethics in the Use of Police Intelligence - Manurung, Agustinus; Kurniati, Yeti; RAS, Hernawati (Formosa Journal of Social Sciences (FJSS), 2024)
This research analyzes the role of professional ethics in the context of the use of intelligence by law enforcement agencies, with a focus on the police. Through a literature study approach, the professional ethics framework in police law is examined to understand how the collection, analysis and use of intelligence information is regulated. Next, the impact of violations of professional ethics in the use of police intelligence on human rights, individual privacy, and the integrity of law enforcement agencies is analyzed. This study concludes that maintaining compliance with the principles of professional ethics is essential in maintaining a balance between public safety and the protection of individual human rights